Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the equation \(\sqrt[4]{2 x-8}+\sqrt[4]{2 x+8}=0\), we look at each provided option to determine which represents a valid, practical step.
First, consider the original equation:
[tex]\[ \sqrt[4]{2 x-8} + \sqrt[4]{2 x+8} = 0 \][/tex]
Here, \(\sqrt[4]{y}\) denotes the fourth root of \(y\), or \(y^{1/4}\).
Next, we will analyze each of the options given:
1. Option 1:
[tex]\[ (\sqrt[4]{2 x-8})^3 = -(\sqrt[4]{2 x+8})^3 \][/tex]
Writing this in exponent form:
[tex]\[ (2 x - 8)^{3/4} = - (2 x + 8)^{3/4} \][/tex]
This is not a valid step because raising both sides to the third power does not simplify the root in a manner consistent with our original problem, and the right side introduces unnecessary complexity.
2. Option 2:
[tex]\[ (\sqrt[4]{2 x-8})^3 = (-\sqrt[4]{2 x+8})^3 \][/tex]
In exponent form:
[tex]\[ (2 x - 8)^{3/4} = [-(2 x + 8)^{1/4}]^3 \][/tex]
This option simplifies similarly as option 1 and is not a valid step. The right-hand side adds unnecessary complexity by involving a negative sign inside a higher power.
3. Option 3:
[tex]\[ (\sqrt[4]{2 x-8})^4 = -(\sqrt[4]{2 x+8})^4 \][/tex]
In exponent form:
[tex]\[ (2 x - 8)^{4/4} = - (2 x + 8)^{4/4} \][/tex]
Simplifying each side:
[tex]\[ 2 x - 8 = - (2 x + 8) \][/tex]
This results in a contradiction since it implies:
[tex]\[ 2x - 8 = -2x - 8 \][/tex]
[tex]\[ 4x = 0 \][/tex]
[tex]\[ x = 0 \][/tex]
Substitution back into the original equation does not confirm practical elimination of the root terms.
4. Option 4:
[tex]\[ (\sqrt[4]{2 x-8})^4 = (-\sqrt[4]{2 x+8})^4 \][/tex]
In exponent form:
[tex]\[ (2 x - 8)^{4/4} = [-(2 x + 8)^{1/4}]^4 \][/tex]
Simplifying each side:
[tex]\[ 2 x - 8 = (-(2 x + 8))^4 \][/tex]
[tex]\[ 2 x - 8 = (2 x + 8) \][/tex]
It means:
[tex]\[ 2x - 8 = -[2x + 8] \][/tex]
[tex]\[ x = 0 \][/tex]
Solving which validates \(2x - 8 = -(2 x + 8 )\),
Therefore, the correct, practical step in solving the given equation is represented by:
[tex]\[ (\sqrt[4]{2 x-8})^4 = (-\sqrt[4]{2 x+8})^4 \][/tex]
Thus, Option 4 is correct.
First, consider the original equation:
[tex]\[ \sqrt[4]{2 x-8} + \sqrt[4]{2 x+8} = 0 \][/tex]
Here, \(\sqrt[4]{y}\) denotes the fourth root of \(y\), or \(y^{1/4}\).
Next, we will analyze each of the options given:
1. Option 1:
[tex]\[ (\sqrt[4]{2 x-8})^3 = -(\sqrt[4]{2 x+8})^3 \][/tex]
Writing this in exponent form:
[tex]\[ (2 x - 8)^{3/4} = - (2 x + 8)^{3/4} \][/tex]
This is not a valid step because raising both sides to the third power does not simplify the root in a manner consistent with our original problem, and the right side introduces unnecessary complexity.
2. Option 2:
[tex]\[ (\sqrt[4]{2 x-8})^3 = (-\sqrt[4]{2 x+8})^3 \][/tex]
In exponent form:
[tex]\[ (2 x - 8)^{3/4} = [-(2 x + 8)^{1/4}]^3 \][/tex]
This option simplifies similarly as option 1 and is not a valid step. The right-hand side adds unnecessary complexity by involving a negative sign inside a higher power.
3. Option 3:
[tex]\[ (\sqrt[4]{2 x-8})^4 = -(\sqrt[4]{2 x+8})^4 \][/tex]
In exponent form:
[tex]\[ (2 x - 8)^{4/4} = - (2 x + 8)^{4/4} \][/tex]
Simplifying each side:
[tex]\[ 2 x - 8 = - (2 x + 8) \][/tex]
This results in a contradiction since it implies:
[tex]\[ 2x - 8 = -2x - 8 \][/tex]
[tex]\[ 4x = 0 \][/tex]
[tex]\[ x = 0 \][/tex]
Substitution back into the original equation does not confirm practical elimination of the root terms.
4. Option 4:
[tex]\[ (\sqrt[4]{2 x-8})^4 = (-\sqrt[4]{2 x+8})^4 \][/tex]
In exponent form:
[tex]\[ (2 x - 8)^{4/4} = [-(2 x + 8)^{1/4}]^4 \][/tex]
Simplifying each side:
[tex]\[ 2 x - 8 = (-(2 x + 8))^4 \][/tex]
[tex]\[ 2 x - 8 = (2 x + 8) \][/tex]
It means:
[tex]\[ 2x - 8 = -[2x + 8] \][/tex]
[tex]\[ x = 0 \][/tex]
Solving which validates \(2x - 8 = -(2 x + 8 )\),
Therefore, the correct, practical step in solving the given equation is represented by:
[tex]\[ (\sqrt[4]{2 x-8})^4 = (-\sqrt[4]{2 x+8})^4 \][/tex]
Thus, Option 4 is correct.
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.